h - Squires, V. R.; Ebooks Corporation (Wallingford : CABI, 2009)
Addressing the issues of greater climate extremes in the future, this book discusses both new approaches and past successes and failures in order to provide the necessary insight to develop sustainable rangeland management strategies, drawing on regional case studies and lessons learned from Australia, Canada and the USA.
Contenido: About the Editors; Contributors; Preface; Acknowledgements; PART I: INTRODUCTION; PART II: MECHANISMS OF RANGELAND DEGRADATION AND RECOVERY; PART III: CASE STUDIES OF DEGRADATION AND RECOVERY; PART IV: THE FUTURE {80}{93} HOW TO PREVENT THE NEXT MAJOR DEGRADATION EPISODE; Index
Libro electronico adquirido a perpetuidad con la editorial CABI
Keywords: DEGRADACION DE LA TIERRA -- CHINA; MANTENIMIENTO DE PRADERAS -- ESTUDIO DE CASOS; PRADERAS